2020
DOI: 10.3390/ma13081871
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Lagrangian-Inverse Method for Evaluating the Dynamic Constitutive Parameters of Concrete

Abstract: The dynamic constitutive behaviors of concrete-like materials are of vital importance for structure designing under impact loading conditions. This study proposes a new method to evaluate the constitutive behaviors of ordinary concrete at high strain rates. The proposed method combines the Lagrangian-inverse analysis method with optical techniques (ultra-high-speed camera and digital image correlation techniques). The proposed method is validated against finite-element simulation. Spalling tests were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“… where is the static strength and is the dynamic maximal compression stress. When analyzing the dynamic properties of concrete by an SHPB device, the increase rate of the dynamic strength is often evaluated by the relationship between DIF and the logarithm of strain rate [ 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… where is the static strength and is the dynamic maximal compression stress. When analyzing the dynamic properties of concrete by an SHPB device, the increase rate of the dynamic strength is often evaluated by the relationship between DIF and the logarithm of strain rate [ 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic mechanical properties of concrete materials have attracted much attention, and the Split Hopkinson Pressure Bar (SHPB) has been used as a common testing device to evaluate materials' impact performance. The strain rate sensitivity is proven to be one of the significant properties of concrete [28][29][30][31][32][33]. In recent years, some researchers found that severe environmental factors would seriously deteriorate the dynamic performance of concrete [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Ding et al introduced multichannel photon Doppler velocimeter (PDV) technology on the basis of the "nV + T0" analysis method and obtained the dynamic constitutive relationship of PMMA [138]. In the year of 2020, Yu et al combined the Lagrangian inverse analysis method with optical technology and proposed an improved "lsv + nv" analysis method to obtain the dynamic constitutive behavior of ordinary concrete under high-strain-rate loading [139]. All the above studies confirm the effectiveness and reliability of the combination of the Lagrangian analysis method and the split-Hopkinson pressure bar technique.…”
Section: Application Of Lagrangian Analysis Methods To Impact Test Of...mentioning
confidence: 99%
“…For a traction separation model, the stiffness of the interface relating the nominal traction stress to the separation displacement can be carried over to a cohesive layer of the initial thickness, T 0 , as described in Equation (14).…”
Section: Cohesive Elements Of Itzmentioning
confidence: 99%
“…[ 5 , 6 , 7 , 8 , 9 ]. Especially for brittle materials, the influence of the boundary conditions has a pronounced effect on the mechanical performance of the quickly softening regime caused by the evolution of the inherent damage [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%